TÁR: power hierarchies, politic and conductors (Orfeu, 2023)
In his film TÁR, the director Todd Field uses the universe of classical music as a background to reflect on the several structures of power. Inversely, the aim of this article is to use the film to discuss the backstage of the political relations linked to the role of orchestra conductor. Thus, throughout this text, some moments of the film will be analyzed and confronted with historical events involving real personalities from the context of classical music. The intention is to consider how the role of conductor was transformed, moving from an autocratic posture to a collaborative conduct. The technical literature from the area of conducting will be used for comparisons. Some writings of Norberto Bobbio and Hannah Arendt are used to ground the reflections on power and politics. As conclusion, it is observed that, despite the desired change in the conductor's behavior advocated in the literature, in Brazil, the power relations between politicians and conductors remain practically unchanged.
Keywords: politic power; power hierarchies; conductors; TÁR; film analysis